1994
DOI: 10.2223/jped.726
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Vaccine: overview about the protective efficacy in different high risk groups and new progress in the development of a conjugate Pneumococcal Vaccine

Abstract: ResumoA autora apresenta uma revisão da literatura mais recente a respeito das vacinas polissacarídicas contra o pneumococo, enfatizando as controvérsias a respeito da eficácia vacinal em diferentes grupos de risco e as dificuldades para o desenvolvimento de novas vacinas conjugadas com maior imunogenicidade e capacidade de estimular a produção de anticorpos em lactentes. J. Pediatr. (Rio). 1994; 70(2):75-81: vacina antipneumocó-cica, Streptococcus pneumoniae, imunização. AbstractThe author presents a review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The most commonly used polysaccharide vaccine, PPV23 ( Pneumovax ® , Merck), formulated with 23 different pneumococcal serotypes (1, 2, 3, 4, 5, 6b, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19F, 19A, 20, 22F, 23F, and 33F) has been available since 1983 in certain age categories, but is poorly immunogenic in young children and has no effect on nasopharyngeal carriage [57,58,81]. To improve the immunogenicity for children under two years of age, a heptavalent conjugate vaccine, PCV7 ( Prevnar ® , Wyeth), formulated with serotypes 4-, 6B-, 9V-, 14-, 18C-, 19F-, and 23F-specific polysaccharides individually conjugated to DT mutant CRM197, was licensed in 2000 for a routine national vaccination campaign in US Studies with Prevnar ® , in which >37,000 children showed 94% prevention of invasive pneumococcal diseases [82,83].…”
Section: Streptococcus Pneumoniamentioning
confidence: 99%
“…The most commonly used polysaccharide vaccine, PPV23 ( Pneumovax ® , Merck), formulated with 23 different pneumococcal serotypes (1, 2, 3, 4, 5, 6b, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19F, 19A, 20, 22F, 23F, and 33F) has been available since 1983 in certain age categories, but is poorly immunogenic in young children and has no effect on nasopharyngeal carriage [57,58,81]. To improve the immunogenicity for children under two years of age, a heptavalent conjugate vaccine, PCV7 ( Prevnar ® , Wyeth), formulated with serotypes 4-, 6B-, 9V-, 14-, 18C-, 19F-, and 23F-specific polysaccharides individually conjugated to DT mutant CRM197, was licensed in 2000 for a routine national vaccination campaign in US Studies with Prevnar ® , in which >37,000 children showed 94% prevention of invasive pneumococcal diseases [82,83].…”
Section: Streptococcus Pneumoniamentioning
confidence: 99%